Glycolysis of polycarbonate wastes with microwave irradiation - Nikje, M. M. (Polimery, 2011)
Polycarbonate contained in waste compact discs have been glycolized with ethylene glycol using microwave irradiation in the presence of sodium hydroxide as catalyst in order to obtain bisphenol A (BPA) as the sole product. The influence of various parameters such as the concentration of the alkali metal catalyst and microwave irradiation power on product yield was studied in detail. The recovered BPA was analyzed with spectroscopic methods (1H NMR, 13C NMR, FT-IR) and the obtained results compared with standards.